Longitudinal Survey of Trainee Case Log Entry for Carotid Endarterectomy: Trends in Neurological, General and Vascular Surgery. (16th November 2020) - White, Michael D; Agarwal, Nitin; Alan, Nima
Abstract: INTRODUCTION: Multiple surgical specialties perform carotid endarterectomy. As indications for carotid endarterectomy narrows, neurosurgery residents are less exposed to this procedure. METHODS: ACGME case log reports were retrospectively reviewed from 2013 to 2019 for neurological, general, and vascular surgery residencies, and vascular surgery fellowship. These annual reports contain the mean number of logged cases for graduating trainees and their level of participation. We analyzed trends in logged carotid endarterectomies over the study period. We compared mean number of logged cases between specialties and their respective required minimum numbers. RESULTS: Neurosurgery residents (13.5 ± 0.76) performed significantly more carotid endarterectomies than their counterparts in general surgery (9.4, ± 0.34, P < . 01), but less in integrated vascular surgery (57.7 ± 0.88) and vascular surgery fellowship (47.9 ± 0.79, both P < . 001). The only statistically significant change over the study period was a decline in mean number of cases logged by general surgery residents at -0.4 cases/year ( P < . 001). Trainees in all specialties reported around twice as many cases as the respective ACGME required minimum numbers. Neurosurgery residents demonstrated a significant increase in participation as lead surgeon by 0.7 cases/year ( P  = 0.04) and a concurrent decline as senior surgeons by 1.4 cases/year ( P < . 01). CONCLUSION: Neurosurgery residents exceeded their minimum requirements for carotid endarterectomy, with increasing trend in higher level of participation. But neurosurgery residents' exposure to this procedure was far less significant than their colleagues in vascular surgery, a gap that may widen over time and should be addressed proactively.